The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1029/2018tc005204
|View full text |Cite
|
Sign up to set email alerts
|

The Spanish‐Portuguese Central System: An Example of Intense Intraplate Deformation and Strain Partitioning

Abstract: The intraplate deformation of Iberia during the Cenozoic produced a series of ranges and deformation belts with a wide variety of structural trends. The Spanish‐Portuguese Central System is the most prominent feature crossing over the whole of central Iberia. It is a large thick‐skinned crustal pop‐up with NE‐SW to E‐W thrusts. However, the 500‐km‐long left‐lateral strike‐slip Messejana‐Plasencia fault, also NE‐SW oriented, bends these thrusts to produce NE‐SW local paleostresses close to the fault, which seem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 55 publications
6
43
0
2
Order By: Relevance
“…The differences below the CS affect the depth as well as the geometry of the crust-mantle interface. The Moho discontinuity in Diaz et al (2016) presents a rather flat geometry, depicting a little 1 km thick root. The results from gravity inversion, while being closer to our results regarding crustal thickness, are highly influenced by the inclusion of the topography in the inversion procedure.…”
Section: Lower Crustmentioning
confidence: 99%
See 2 more Smart Citations
“…The differences below the CS affect the depth as well as the geometry of the crust-mantle interface. The Moho discontinuity in Diaz et al (2016) presents a rather flat geometry, depicting a little 1 km thick root. The results from gravity inversion, while being closer to our results regarding crustal thickness, are highly influenced by the inclusion of the topography in the inversion procedure.…”
Section: Lower Crustmentioning
confidence: 99%
“…The granites of the western sector correspond to the Avila Batholith, which is a vast association of igneous rocks. The current knowledge of the crustal and lithospheric structure of the Central System comes mainly from geophysical studies such as seismic data (Suriñach and Vegas, 1988;Diaz et al, 2016) and inversion and forward modelling of potential-field data (Tejero et al, 1996;de Vicente et al, 2007;Torne et al, 2015). These studies have found a crustal thickness in the range of 31 to 35 km, showing a thickening underneath the Central System with respect to the surrounding basins.…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether these thrust flats reactivate or cut a previous extensional detachment is uncertain (no clear synextensional growth geometries can be identified in their hanging walls and this prevents the characterization of extensional fault geometries at depth; Figure 13a). They outline an imbricate thrust system soled by a décollement in the shallow basement (Figure 8a, basement-involved thin-skinned tectonics, Pfiffner, 2006) that resembles the structural style in the eastern Central System, to the west of the study area (Figure 2;De Vicente et al, 2018). Thickness variations in relation to the Sierra de Arcos thrust (named as Sierra de Arcos Fault in Figure 13a) are in agreement with its role as the northern boundary of the Oliete subbasin (Casas et al, 1997;Soria, 1997) that (i) thinned progressively toward the east (cf.…”
Section: Distribution Of Basement-involved and Cover-detached Structumentioning
confidence: 99%
“…occupy intra-plate positions. Both are the result of plate tectonics in the Mediterranean domain as well as of distributed strain upon Africa-Europe convergence (Dewey et al, 1989;Jolivet et al, 2008;de Vicente et al, 2018).…”
Section: Geological Settingmentioning
confidence: 99%